Comparison Between Phenotypic Confirmatory Test & Double Disc Synergy Test in Detection of Extended Spectrum b-Lactamases Producers Among Gram-Negative Bacilli (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Extended-Spectrum b-Lactamases (ESBLs) producing bacteria are increasing in number and causing more severe infections because of their continuous mutation and multidrug resistance property which make its treatment difficult. Thus reliable, sensitive and low cost method to detect ESBLs producers, therefore, is of major interest. The present study was undertaken to compare the sensitivity between double disc synergy test & phenotypic confirmatory test to detect ESBLs producing bacteria.Methods: All the isolates were identified by standard procedure of identification & isolated gram-negative bacteria initially screened by Minimum Inhibitory Concentration (MIC) ESBLs breakpoints. Then suspected ESBLs producers are confirmed by double disc synergy test & phenotypic confirmatory test.Results: In the present study, total 176(74.89%) bacterial strains were isolated from 235 samples of wound swab & pus, and urine. Among the isolates, 150(85.23%) were gram-negative and 26(14.77%) were gram-positive bacteria. The gram-negative bacteria were screened for suspected ESBLs & then subjected to confirmatory test where Phenotypic Confirmatory Test (PCT) detected 89(62.68%) and Double Disc Synergy Test (DDST) detected 74(52.11%) ESBL producers. So 15(10.57%) isolates were missed by double disc synergy test. In this study, we determined sensitivity, specificity, positive predictive value & negative predictive value of Phenotypic Confirmatory Test (PCT) were 100%, 77.9%, 83.1% & 100% respectively and those of Double Disc Synergy Test (DDST) were 83.1%, 100%, 100%, and 77.9% respectively.Conclusion: Between these two tests, phenotypic confirmatory test found to be more sensitive procedure than double disc synergy test for the detection of ESBLs producing organisms.Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 3-8